1988
DOI: 10.1002/ajim.4700130304
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanates and respiratory disease: Current status

Abstract: This paper reviews the known respiratory effects of isocyanates. There is good evidence to indicate that isocyanates: cause chemical bronchitis/pneumonitis; are potent pulmonary sensitizers capable of causing "isocyanate asthma"; cause nonspecific airways disease, including chronic bronchitis; can induce a general asthmatic state; and can cause hypersensitivity pneumonitis. Similar dose-response relationships are seen for both acute and chronic effects. There are plants operating in which exposures are well co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 65 publications
0
44
0
4
Order By: Relevance
“…According to Mapp et al (26), the estimated prevalence of WRA among painters using isocyanate-based aerosol paints was 7.1 %. Toluene diisocyanae (TDI), methylene diphenyldiisocyanate (MDI), and hexamethilene diisocyanate (HDI) are known causative agents of allergic OA (27). Although the isocyanate-induced effects are widely cited, their pathways, as well as the importance of intensity, duration, and frequency of exposure are still not well understood (9,20).…”
Section: Discussionmentioning
confidence: 99%
“…According to Mapp et al (26), the estimated prevalence of WRA among painters using isocyanate-based aerosol paints was 7.1 %. Toluene diisocyanae (TDI), methylene diphenyldiisocyanate (MDI), and hexamethilene diisocyanate (HDI) are known causative agents of allergic OA (27). Although the isocyanate-induced effects are widely cited, their pathways, as well as the importance of intensity, duration, and frequency of exposure are still not well understood (9,20).…”
Section: Discussionmentioning
confidence: 99%
“…The indirect evidence reported, however, would suggest that it would have to be an unusual disease model which would need to be invoked that could exclude the possible mechanism of change in individual risk factors so that the absence of an acute reaction would eliminate the possibility of a chronic effect related to the acute exposure. Occupational exposure,[3][4]7,Occupational exposure 4243,55,120,140,215,Protective clothing,10,[36][37][38][39][40][221][222]225 52,205n carcinogenicity,[97][98][99][100][101]Psoriasin,[170][171]105,[169][170]Psychoactive drug testing,46,[172][173]397 378-380 chlorine gas, 401…”
Section: Discussionmentioning
confidence: 99%
“…55 In 1951, case reports of isocyanate-related pulmonary effects called attention to a new occupational asthma.6 Sensitization was reported to occur as early as after only one high exposure, 5 7 but onset could also be delayed for a number of years after first exposure.,"r Unlike with high molecular weight agents which cause occupational asthma, however, further study of isocyanate asthma cases showed that measurable IgE and airway hyperreactivity was not invariably an essential feature. ",' 6 ,'I The course of isocyanate asthma includes the fact that as many as half of seriously affected workers who leave work do not recover.…”
Section: Isocyanatesmentioning
confidence: 99%
See 2 more Smart Citations